2023
DOI: 10.1186/s40798-023-00638-9
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Curtain: Prevalence of Symptoms of Depression, Generalised Anxiety and Eating Disorders in 147 Professional Dancers from Six Opera Houses or State Theatres

Astrid Junge,
Anja Hauschild

Abstract: Background Mental health problems cover a wide spectrum. Depression and anxiety disorders are the most frequent mental health problem in the general population and in elite athletes. The aim of the present study was to assess the prevalence of symptoms of depression, generalised anxiety disorder and eating disorders in professional dancers, to compare the results between genders and to the general population and to analyse potential determinants. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…While in our study the prevalence was substantially higher in female than in male dancers, no gender difference was found in dance students [ 19 ]. A higher prevalence of mental health symptoms in women than in men has been reported for general populations [ 34 , 35 ], elite athletes [ 36 , 37 ] and in professional dancers [ 38 ]. Similar to the general population, the most frequent symptoms in the present study were “depression, low mood” and “generalized anxiety”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in our study the prevalence was substantially higher in female than in male dancers, no gender difference was found in dance students [ 19 ]. A higher prevalence of mental health symptoms in women than in men has been reported for general populations [ 34 , 35 ], elite athletes [ 36 , 37 ] and in professional dancers [ 38 ]. Similar to the general population, the most frequent symptoms in the present study were “depression, low mood” and “generalized anxiety”.…”
Section: Discussionmentioning
confidence: 99%
“…Potential reasons for mental health problems of dancers (e.g. body image pressure, chronic injury, career uncertainty, training load) have been discussed in the literature [ 38 40 ]. However, few preventive interventions have been developed and evaluated [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 Research shows that coping with these challenges is taking a toll on dancers’ physical and mental health and that dancers appear more prone to certain mental health challenges compared with the general population. 5 For instance, van Winden et al indicated that 39.4% of pre-professional contemporary dancers in their study reported mental health issues that affected their mental well-being and physical health. 6 A more recent study uncovered that 20.8% of the participating professional ballet, contemporary and revue dancers had moderate symptoms of either depression, anxiety or eating disorders and that, compared with a general population, this prevalence was twice as high in female dancers.…”
Section: Introductionmentioning
confidence: 95%
“… 6 A more recent study uncovered that 20.8% of the participating professional ballet, contemporary and revue dancers had moderate symptoms of either depression, anxiety or eating disorders and that, compared with a general population, this prevalence was twice as high in female dancers. 5 …”
Section: Introductionmentioning
confidence: 99%